2022-RA-1272-ESGO Cost-effectiveness of risk-reducing surgery for breast and ovarian cancer prevention: a systematic review. (20th October 2022) - Wei, Xia; Oxley, Samuel; Sideris, Michail; Kalra, Ashwin; Legood, Rosa; Manchanda, Ranjit
Abstract : Introduction/Background: Risk-reducing mastectomy (RRM) and salpingo-oophorectomy (RRSO) are the gold standard preventative strategies for women at high-risk of breast cancer (BC)/ovarian cancer (OC). Risk-reducing early-salpingectomy followed by delayed-oophorectomy (RRESDO) is being trialled as an alternative to RRSO. Opportunistic bilateral salpingectomy (OBS) during gynaecological surgery has been proposed as a potential approach to prevent OC in general population. We performed a systematic review of the published evidence on cost-effectiveness of RRM/RRSO/RRESDO for BC/OC prevention in intermediate/high-risk women, and OBS in baseline-risk. Methodology: We searched major databases to December 2021. We included economic evaluation studies reporting on cost-effectiveness/cost-utility outcomes in women at high-risk of BC/OC undergoing RRM/RRSO/RRESDO, or baseline OC risk undergoing OBS. Results: Our search yielded 5801 citations; 22 studies were included. Eight studies concluded that RRM/RRSO individually or in combination were cost-effective compared to surveillance/no surgery for unaffected BRCA1/2 carriers, while one study found that RRESDO was cost-effective. Two studies on women at low/intermediate OC-risk specified that RRSO was cost-effective at OC lifetime risks of ≥4% (pre-menopausal) and ≥5% (post-menopausal women). These results were partially sensitive to initial age, uptake rates, cancer risk-reduction, and disutility following surgery. Four studies concluded that the addition of OBS to hysterectomy was cost-effective for OC prevention in the general population. Similarly, OBS was cost-effective as an alternative to sterilisation via laparoscopy (four studies) or at caesarean section (two studies). However, given the paucity of high-quality long-term outcome data, the uncertainty of level of risk-reduction, lack of disutility data, there remains some uncertainty around cost-effectiveness. Conclusion: This systematic review confirms that RRM/RRSO are cost-effective, and RRESDO is potentially cost-effective in women at intermediate/high risk of BC/OC in several high-income countries. Although OBS seems to be a potentially cost-effective option for OC risk-reduction, there is a need for high-quality evidence around its long-term including oncological outcomes.